2015
DOI: 10.3390/s150305081
|View full text |Cite
|
Sign up to set email alerts
|

A High Speed CMOS Image Sensor with a Novel Digital Correlated Double Sampling and a Differential Difference Amplifier

Abstract: In order to increase the operating speed of a CMOS image sensor (CIS), a new technique of digital correlated double sampling (CDS) is described. In general, the fixed pattern noise (FPN) of a CIS has been reduced with the subtraction algorithm between the reset signal and pixel signal. This is because a single-slope analog-to-digital converter (ADC) has been normally adopted in the conventional digital CDS with the reset ramp and signal ramp. Thus, the operating speed of a digital CDS is much slower than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this paper, the mechanism and influence of non-ideal factors of a spike-based image sensor are discussed. As the pixel continuously perceives the scene information in the time domain, it is impossible to eliminate the influence of photo response non-uniformity (PRNU) by the time domain correlation double sampling method [14,15]. However, based on characteristics of PRNU, a coefficient matrix obtained by the measurement is used to suppress its effect.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the mechanism and influence of non-ideal factors of a spike-based image sensor are discussed. As the pixel continuously perceives the scene information in the time domain, it is impossible to eliminate the influence of photo response non-uniformity (PRNU) by the time domain correlation double sampling method [14,15]. However, based on characteristics of PRNU, a coefficient matrix obtained by the measurement is used to suppress its effect.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the conventional high-speed imaging methods for solid-state image sensors can be classified into two categories. One is the use of parallel readout imaging scheme [ 6 , 7 , 8 ]. Tochigi et al had demonstrated a global-shutter high-speed CMOS image sensor with a readout speed of 1-Tpixel/s in burst video and 780-Mpixel/s continuous [ 9 ].…”
Section: Introductionmentioning
confidence: 99%